The impact of workplace psychological violence on clinical nurses' turnover intention: the mediating role of perceived stress - Tan, Lin; Zheng, Shouqi; Zhong, Xiaoli; Han, Ying; Xia, Lin; Fan, Yuting; He, Lin (Frontiers in Public Health, 2025)
BackgroundThe global shortage of nurses has become a significant health emergency, and nurses' turnover intention is a key influencing factor, serving as an important predictor of actual turnover rates. However, studies integrating workplace psychological violence, perceived stress, and turnover intention in the same mediation model are still limited, so there is an urgent need to explore in depth the mediating effect of perceived stress between workplace psychological violence and turnover intention.ObjectiveTo examine the mediating effect of nurses' perceived stress on the relationship between workplace psychological violence and turnover intention among nurses in tertiary general hospitals in Southwest China.MethodsBetween October 2024 and March 2025, 798 nurses from nine tertiary general hospitals in southwest China were selected by a convenience sampling method for the study. A cross-sectional survey was conducted using the General Information Questionnaire, Turnover Intention Scale, Psychological Violence in the Workplace Scale, and Perceived Stress Scale. The mediating effect was examined using SPSS and PROCESS Model 4.ResultsTurnover intention was positively correlated with Workplace Psychological Violence (r = 0.364, P < 0.001) and with Perceived Stress (r = 0.423, P < 0.001), and Workplace Psychological Violence was positively correlated with Perceived Stress (r = 0.486, P < 0.001). Perceived stress showed a partial mediating effect in the influence of psychological violence in the workplace on turnover intention, with a mediating effect value of 0.129, and the mediating effect accounted for 36.96% of the total effect.ConclusionPerceived stress demonstrates a mediating effect between workplace psychological violence and turnover intention among nurses. Nursing managers can reduce perceived stress among nurses by decreasing workplace psychological violence, thus reducing nurses' turnover intention, improving nurses' job satisfaction and mental health, and promoting the stability and sustainable development of the nursing team.